Зіставлення вимог вітчизняних і міжнародних стандартів до труб з корозійностійкої сталі для ядерних енергетичних установок - Буряк, Т.М.; Ярошенко, Н.В. (Ядерна та радіаційна безпека, 2014)
Проаналізовано стандарти і технічні умови (ГОСТ, ТУ, ASTM, EN) на труби з корозійностійкої сталі серії Х18Н10Т (ТР321), що використовуються в конструкціях АЕС. Обґрунтовано доцільність оптимізації вимог до вітчизняних труб згідно з міжнародними стандартами та рекомендаціями стосовно наближення до євронорм. Проанализированы стандарты и технические условия (ГОСТ, ТУ, ASTM, EN) на трубы из коррозионностойкой стали серии Х18Н10Т (ТР321), которые используются в конструкциях АЭС. Обоснована целесообразность оптимизации требований к отечественным трубам в соответствии с международными стандартами и рекомендациями по приближению к евронормам. The paper presents review of standards and specifications (GOST, TU, ASTM, EN) for stainless steel of X18H10T (TP321) series used in NPP structures. It gives a comparative analysis of steel chemical composition, structure, mechanical properties, non-destructive testing of pipes and others. Requirements for seamless pipes (hot- and cold-worked) and welding are considered. The paper is aimed at displaying mismatches between pipes under different standards. National standards should be put in compliance with European regulations. The activity should meet European standards. Therefore, requirements for national NPP pipes should be put in compliance with international standards, rules and regulations. Recommendations are given on the approach to emission class, namely a gradual transition to the modified type identical to the introduction of amended and adapted national technologies and methods of control.